Propuesta para la Creación de una Caja de Ahorro en la Junta Administradora de Agua Potable de la Parroquia Chantaco, Cantón Loja - Córdova Campoverde, Faviola Vanessa (2017)
This study aims to determine the feasibility of creating a savings in the Administrative Board of Drinking Water Chantaco parish, in order to facilitate financing through loans, to engage in their own businesses and their while fostering a savings culture, improving the quality of life of its users, for it was necessary to carry out a market study, technical study, administrative and legal study and an economic and financial study, the same that allowed to know the feasibility of the proposal. It begins with the literature review based on books with information according to the development of the project, related to popular finance and the process that must be followed to carry out an investment project. In addition, different methods and techniques were applied to each study. The Market Study was carried out through the collection of information through surveys and interviews, with which the target market was calculated. Potential partners represented by the total market to study which is composed of 280 members. The effective members constituted by the people who would like to be future partners of the Savings Bank equivalent to 94% that is 260 possible partners. Through a Technical Study, the second objective was fulfilled, which served to detail the exact location where the savings bank will operate, the size of its facilities and the human, material and economic resources that will be required to The implementation of the project. Likewise, in the Administrative-Legal Study, the legal bases for the creation of legal personality and the regulatory bodies to which the Savings Bank was governed, such as the Popular and Solidarity Economy Law and its respective regulations, were determined; As well as its functional-organizational structure, through which its statutes and hierarchical order of officials were determined. Finally, the Economic-Financial Study was determined by calculating the investment that is $ 13,927.23 the budgets of both revenue and costs and finally the financial indicators; Which resulted in a feasible project to be implemented in the Chantaco Parish Management Board, ie, it is profitable and sustainable over time. Finally, conclusions and recommendations were developed, based on the results obtained with the preparation of this thesis